Molecular Characterisation And Pathogenicity Of Infectious Bursal Disease Virus Isolated In Iran - Bahmaninejad, Mohammad Ali (2004)

(untitled)
Infectious bursal disease (IBD) is one of the most important diseases among the poultry industries in Iran. Ten IBD virus (IBDV) isolates were obtained from IBD field outbreaks. These isolates were from the vaccinated and non IBD vaccinated broiler and layer flocks in Iran and were designated as IR197, IR297, IR198, IR298, IR398, IR199, IR299, IR399, IR499 and IR599. These isolates showed clinical signs, mortality, gross and histological lesions in commercial chickens that were typical of IBD during field outbreaks. The Iranian IBDV isolates were isolated and identified by conventional methods including agar gel precipitation test (AGPT), egg inoculation, chicken embryo fibroblast (CEF) cell culture, transmission electron microscopy (TEM), and immunoperoxidase staining (IPS) as IBDV. These isolates could not propagate onto CEF cell culture except IR298 isolate, which produced cytopathic effect (CPE) in cell culture. IR298 and IR499 isolates were inoculated into 28-day-old specific pathogen free (SPF) chicken; IR298 isolate did not produce any mortality and the gross lesions in SPF chickens but the bursa of Fabricius was atrophied, whereas IR499 isolate induced 70% mortality, gross and histological lesions which were typical of very virulent (vv) vvIBDV. All isolates were further characterised by molecular techniques based on RT-PCR-RFLP and nested PCR. The hypervariable region of VP2 gene were amplified and sequenced. The phylogenetic tree was constructed based on aligned sequences of the Iranian isolates and published IBDV strains. All the isolates had the characteristics of vvIBDV strain similar to the earlier reports, except IR298 isolate showed the characteristics of vaccine strain. The phylogenetic tree of the isolates showed that all isolates except IR298 belongs to vvIBDV subgroups of serotype 1. Isolates IR197, IR299, IR399, IR398, IR499 and IR599 formed the distinct sub branch within the subgroup of vvIBDV strain. IR298 isolate was located within the subgroup of the vaccine strain. The origin of these isolates could be similar to the vvIBDV strains isolated in Europe, Japan and Hong Kong, whilst IR298 isolate could be similar to the Chinese and Egyptian classical as well as vaccine strains. The IR499 isolate (106.7 EID50) was inoculated in 28-day-old SPF chickens via oral route to determine the response of gut-associated lymphoid tissues (GALT) to vvIBDV isolated in Iran. The GALT were lymphoid cell aggregations at the oesophagus and proventriculus junction, proventriculus and gizzard junction, duodenum, Meckel’s diverticulum, caecal tonsil, ileum and bursa of Fabricius. Among the organs, the bursa of Fabricius showed the most severe lesions including degeneration, necrosis, inflammation, haemorrhage, follicular lymphoid cells depletion, and follicular cyst formation. The virus induced degeneration, necrosis and depletion in the lymphoid cells of the GALT in the rest of the organs at days 2, 3 and 4 post inoculation (pi). The finding in this study showed that the acidic (pH 2.6) of proventriculus may hamper the infectivity or population of the virus. Thus, the following oral inoculation of vvIBDV, the virus is primary multiplied in the upper part of the GALT, at the junction between the oesophagus and proventriculus within 6 to 12 hours pi, rather than the lower GALT leading to primary viraemia. it was concluded that all the Iranian IBDV isolates were successfully isolated, identified and characterised as vvIBDV (except IR298 isolates) using conventional and molecular methods. They showed similar characteristic of vvIBDV reported from Europe, Japan and Hong Kong, except IR298 isolate showed the characteristics similar to the Chinese and Egyptian classical strains as well as vaccine strains. Inoculation of IR499 isolate (vvIBDV) in the SPF chickens produced the most severe lesions in the bursa of Fabricius at days 2, 3, 4 and 10 pi when compare to the GALT in the other organs.